Effect of murine cytomegalovirus infection on mitogen responses in genetically resistant and susceptible mice. - Allan, J E (1982)
Suppression of the blastogenic response of spleen cells was found during murine cytomegalovirus infection of the genetically susceptible BALB/c and also the more resistant BALB.K strains of mice. These results were observed for both the T-cell mitogen concanavalin A and the B-cell mitogen lipopolysaccharide. As the viral inoculum was increased, there was greater immunosuppression within each strain, the time of maximum depression coinciding with peak virus titers in the spleen. Although both strains developed similar splenic virus titers and exhibited a similar decrease in the proportion of splenic T-lymphocytes, there was greater suppression of the mitogenic response during sublethal infection of the more susceptible BALB/c strain. The suppression could not be readily accounted for by the presence of suppressor cells or by a change in sensitivity to mitogen. The results suggest that the extent of immunosuppression induced by murine cytomegalovirus is determined in part by host genotype.